Crocodile swim tracks from the latest Cretaceous of Europe. (13th October 2014) - Vila, Bernat; Castanera, Diego; Marmi, Josep; Canudo, José I.; Galobart, Àngel
Abstract : Recently discovered evidence of tracks in the continental beds of the Late Cretaceous Tremp Formation in the southern Pyrenees (NE Iberian Peninsula) has been identified as scratch marks made by buoyant crocodiles. The tracks are preserved in two distinct environments and substrates (marly limestones originating in a littoral mud flat and fine‐grained sandstones deposited in fluvial settings). Most of the crocodylian traces are ascribed to ichnogenus Characichnos, whereas a single plantigrade pes track is assigned to ichnogenus cf. Crocodylopodus . The crocodylian swim traces ( Characichnos ichnofacies) found in the early and late Maastrichtian co‐occur with Brontopodus ichnofacies attributable to terrestrial tetrapods (titanosaur sauropods, cf. Brontopodus ichnogenus; and hadrosaurid ornithopods, Hadrosauropodus ichnogenus). Analysis of the tracks allows the interpretation of palaeoenvironmental settings and track production. Thus, in lagoonal environments, swim tracks of crocodylians were produced during the rise of the water level in successive tide cycles; in fluvial settings, the swim traces of crocodylians were produced within the channel at the low‐water stage. To date, there are no reports of Late Cretaceous crocodylian tracks in Europe, and the studied evidence represents the first and youngest track record of the group in the latest part of the Cretaceous (C29r) in this continent and probably in the world.